Correlation of Environmental Factors Associated with The Incidence of Diarrhea in Under-Five in Indonesia : A Community based Total Sanitation Approach toward Achievement Millennium Development Goals - Inoy Trisnaini; Fadilatus Sukma Ika N; Jumali (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2015)
Background: Diarrhea is a worldwide health problem, especially in the developing countries. Based on WHO (2010) that 58% of under-five deaths were caused by infectious diseases, one on it was diarrhea. Based on Ministry of Health Indonesia (2011), 8.8 million child deaths in the world was 1,3 million caused by diarrhea in 2008, and more than 98% of it occur in 68 the developing countries. In Indonesia 5% of under-five deaths were caused by diarrhea (WHO, 2010). The purpose of this research is to analyze the association between environmental factors with the incidence of diarrhea in under-five.Method: The method used in documentation was by collecting the data from the results of research studies as well as supporting the secondary data sources. The data analysis was descriptive analysis technique.Result: The research results of Eralita (2001), showed that variables had significant correlation with diarrhea were clean water facilities OR=6.610, having latrine OR=2.896, waste water sewage facilities OR=5.967, and solid waste container facilities OR=3.746. The research by Sinthamurniwaty (2006), the risk factor that influence diarrhea in under-five was who do not use clean water source (OR = 2,208). Also, the research results of Rosyidi (2011) at District Lebong, Bengkulu Province showed the variable that associated was location of septic tank OR=4.934. It strengthened by the research of Santoso (2003) in the Sukarta City, that was discovered coliform content in water sources clean. This suggests the existence of contamination by feces as a source of diarrhea disease.Conclusion: There is association between a family privy with incidence of diarrhea, this indicates that environment pollution caused by faces as the source of diarrhea.Keyword: diarrhea in under-five, environmental factors, community based total sanitation